FTY720 inhibits tumor growth and enhances the tumor‐suppressive effect of topotecan in neuroblastoma by interfering with the sphingolipid signaling pathway. Issue 9 (23rd May 2013) - Li, Mei‐Hong; Hla, Timothy; Ferrer, Fernando
Abstract Background Neuroblastoma (NB) is the most common extra‐cranial solid tumor in childhood. Poor outcomes for children with advanced disease underscore the need for novel therapeutic strategies. FTY720, an immunomodulating drug approved for multiple sclerosis, has been investigated in oncology with promising preclinical activities. To date, its effect in NB has not been explored. Herein we describe our preclinical experience with FTY720, alone or in combination with topotecan, and its putative mechanism of action in NB. Procedure MTT assay was performed to assess the effect of FTY720 on cell viability. A NB xenograft model was employed to assess the efficacy of FTY720 on tumor growth. Quantitative real‐time PCR and Western blot were employed to determine changes of mRNA and protein expression, respectively. Liquid chromatography/tandem mass spectrometry was used to measure sphingolipid levels. Results FTY720, but not FTY720‐P induced NB cell death. FTY720 inhibited the growth of NB xenografts and enhanced the tumor‐suppressive effect of topotecan both in vitro and in vivo. FTY720 significantly inhibited sphingosine kinase 2 (SphK2) mRNA and protein expression in NB cells. Pro‐apoptotic sphingosine levels were increased in NB cells and NB xenografts treated with FTY720. FTY720‐induced cell death was caspase‐independent and involved the dephosphorylation of Akt and BAD at Ser136. Conclusions Our data demonstrate that FTY720 has potent preclinical anti‐cancer activity in NB. Its unique death signaling mechanism, interference with the sphingolipid pathway, acts cooperatively with that of topotecan, suggesting that FTY720 related molecules may be useful in NB treatment. Pediatr Blood Cancer 2013;60:1418–1423. © 2013 Wiley Periodicals, Inc.